Chemistry, manufacture and applications of natural rubber - Kohjiya, Shinzo; Ikeda, Yuko, 1956- (Woodhead Publishing in materials., 2021)
Chemistry, Manufacture and Applications of Natural Rubber, Second Edition presents the latest advances in the processing, properties and advanced applications of natural rubber (NR), drawing on state-of-the-art research in the field. Chapters cover manufacturing, processing and properties of natural rubber, describing biosynthesis, vulcanization for improved performance, strain-induced crystallization, self-reinforcement, rheology and mechanochemistry for processing, computer simulation of properties, scattering techniques and stabilizing agents. Applications covered include natural rubber, carbon allotropes, eco-friendly soft bio-composites using NR matrices and marine products, the use of NR for high functionality such as shape memory, NR for the tire industry, and natural rubber latex with advanced applications. This is an essential resource for academic researchers, scientists and (post)graduate students in rubber science, polymer science, materials science and engineering, and chemistry. In industry, this book enables professionals, R & D, and producers across the natural rubber, tire, rubber and elastomer industries, as well as across industries looking to use natural rubber products, to understand and utilize natural rubber for cutting-edge applications.